PENGARUH DANA ALOKASI UMUM TERHADAP BELANJA MODAL DENGAN PERTUMBUHAN EKONOMI SEBAGAI PEMODERASI (Studi Pada Kabupaten/Kota Provinsi Jawa Tengah Tahun 2011-2013) (Students' Journal of Accounting and Banking, 2015)
The local government allocated funds in the form of capital expenditure in the local budget to increase fixed assets. During this shopping areas more widely used for routine spending relatively less productive. The purpose of this study is to prove empirically the effect of General Allocation Fund for Capital Expenditure in the District / City Central Java province in the year 2011-2013 with moderation variables Economic Growth. The population in this study is the Regency / City Central Java Province which consists of 35 District / City. This study uses secondary data such as Realization Report 2011-2013 budget. In this study, the test model for hypothesis testing will be done using Moderated Regression Analysis. The data has been collected and analyzed in advance with the classic assumption test. Based on the results of this study concluded that the General Allocation Fund has a positive influence on Capital Expenditure. Direction regression coefficient is positive, meaning that an increase in the General Allocation Fund will increase capital expenditures. Economic growth does not affect the Capital Expenditure. Economic growth does not moderate the relationship with the general allocation fund capital expenditures.Keywords: General Allocation Fund, Economic Growth and Capital Expenditure